Seven o'clock tales - Blyton, Enid (Mammoth London, 1993)
Meet the mischievous shoemaker who sews a Skippety Spell into the King's shoes; a pixie who finds a shoelace which grants his every wish; and a basketful of brownies on their way to a pary in Fairyland.